The Role of Muslim Families Awareness in Promoting Education for Human Development in Sokoto State, Nigeria - Alkanchi, Hassan Malami; Md Yusoff, Yusmini; Mohammed Zaidan, Ashraf (Jurnal Usuluddin, 2020)
In Muslim society, the family is an organised institution governed by the principles of Islamic teachings. At the global level, education and human development are considered as universally beneficial for human society as a whole. Muslim families have begun to play a pivotal role in promoting awareness of the importance of education for human development within and beyond their family’s context to raise a new level of the importance of education for human development. The objective of this paper is to explore the important roles played by Muslim family awareness on education for human development in Sokoto state, Nigeria. Qualitative methodological approach to data collection and analysis is used in the study. 12 participants were involved, consisting of four (4) for each research subject. Interviews were conducted with family professionals/experts, Muslim family counsellors; Islamic scholars and academicians. The findings of the study reveal that the awareness of Muslim families of education has a positive impact on human development in Sokoto state. Besides that, the study further finds that parents, teachers, and secular/Islamic schools play a pivotal role in promoting human development in Sokoto. Finally, the study offers some implications to help the government, policymakers, stakeholders, religious leaders, and parents to increase awareness of the importance of education for human development. Thus, recommendations from the findings underline the role played by Muslim families on education for human development in Sokoto, Nigeria and elsewhere.